Seven-transmembrane receptor protein RgsP and cell wall-binding protein RgsM promote unipolar growth in Rhizobiales. - Simon Schäper (PLoS Genetics, 2018)
Members of the Rhizobiales (class of α-proteobacteria) display zonal peptidoglycan cell wall growth at one cell pole, contrasting with the dispersed mode of cell wall growth along the sidewalls of many other rod-shaped bacteria. Here we show that the seven-transmembrane receptor (7TMR) protein RgsP (SMc00074), together with the putative membrane-anchored peptidoglycan metallopeptidase RgsM (SMc02432), have key roles in unipolar peptidoglycan formation during growth and at mid-cell during cell division in Sinorhizobium meliloti. RgsP is composed of a periplasmic globular 7TMR-DISMED2 domain, a membrane-spanning region, and cytoplasmic PAS, GGDEF and EAL domains. The EAL domain confers phosphodiesterase activity towards the second messenger cyclic di-GMP, a key regulatory player in the transition between bacterial lifestyles. RgsP and RgsM localize to sites of zonal cell wall synthesis at the new cell pole and cell divison site, suggesting a role in cell wall biogenesis. The two proteins are essential for cell wall biogenesis and cell growth. Cells depleted of RgsP or RgsM had an altered muropeptide composition and RgsM binds to peptidoglycan. RgsP and RgsM orthologs are functional when interchanged between α-rhizobial species pointing to a conserved mechanism for cell wall biogenesis/remodeling within the Rhizobiales. Overall, our findings suggest that RgsP and RgsM contribute to the regulation of unipolar cell wall biogenesis in α-rhizobia.